1996
DOI: 10.1002/(sici)1099-0984(199609)10:3<161::aid-per259>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

The relation between temperament and rate of temporal discounting

Abstract: The present study examines the relationship between several temperamental traits (sensation seeking, extraversion-introversion, and impulsivity)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(36 citation statements)
references
References 41 publications
1
35
0
Order By: Relevance
“…In two studies that examined differences between groups defined on the basis of personality traits, Ostaszewski (1996Ostaszewski ( , 1997 compared extraverts with introverts and high with low impulsive groups (Eysenck, Eysenck, & Barrett, 1985) as well as high and low sensation seekers (Zuckerman, 1971). In both studies, the extravert and high impulsive groups showed steeper discounting of hypothetical delayed rewards than did the introvert and low impulsive groups.…”
Section: Applications To Group Differencesmentioning
confidence: 99%
“…In two studies that examined differences between groups defined on the basis of personality traits, Ostaszewski (1996Ostaszewski ( , 1997 compared extraverts with introverts and high with low impulsive groups (Eysenck, Eysenck, & Barrett, 1985) as well as high and low sensation seekers (Zuckerman, 1971). In both studies, the extravert and high impulsive groups showed steeper discounting of hypothetical delayed rewards than did the introvert and low impulsive groups.…”
Section: Applications To Group Differencesmentioning
confidence: 99%
“…But what if the choice is between a smaller immediate payoff and a larger delayed payoff? Aversion toward waiting (discounting strength) varies among decision makers and may be dependent on individual characteristics, such as age (Green, Myerson, & Ostaszewski, 1999), impulsivity (Alessi & Petry, 2003), and extraversion (Ostaszewski, 1996).…”
Section: Perceptions Of Immediate Vs Delayed Payoffsmentioning
confidence: 99%
“…Thus, motor timing, time estimation and temporal foresight processes have been shown to be impaired in impulsive personalities ( Van den Broek et al 1992;Ostaszewski 1996;Reynolds & Schiffbauer 2004) and in adult impulsiveness disorders such as substance abuse (Reynolds 2006;Wittmann et al 2007a,b), borderline personality disorder (Bazanis et al 2002;Berlin et al 2005) and mania (Bschor et al 2004;Christodouiou et al 2006). They are also impaired in patients with fronto-striatal brain lesions and secondary impulsiveness (Rubia et al 1997;Bechara & Van der Linden 2005).…”
Section: Deficits In Timing Functions In Impulsiveness and Attention-mentioning
confidence: 99%